El proceso de Nulidad Matrimonial en el Derecho Canónico Indiano. Puntos de Contacto con el Motu Proprio Mitis Iudex Dominus Iesus - Terránéo, Sebastián (Anuario argentino de derecho canonico, 2016)
In this article we propose a comparative study among the ancient regime's marriage nnulment process, and the particularities taken into account in the Indian Canonic Law and Pope Francis's motu proprio, Mitis Iudex. Parting from the judicial organization of the Indian Church, and the study of a case presented before the Audience of Buenos Aires's Bishopric, in the first middle of the XVIIth century, common facts are established between both prodecural legislations.